Sliding mode control design for linear systems subject to quantization parameter mismatch - Zheng, Bo-Chao; Park, Ju H. (Journal of the Franklin Institute, 2016)
This paper is concerned with the sliding mode control design for linear systems considering the mismatch between quantization sensitivity parameters generated at the coder and decoder sides. By analyzing the working principle of the encoder/decoder, and the feature of the digital communication channel, a mismatched relation between the quantization parameters is formed by using a time varying ratio model which includes the existing results as special cases. Sequently, based on the established mathematical model, sliding mode control laws are designed to ensure the asymptotical stability of the whole dynamical system. Finally, examples are shown to verify the validity of the theoretical results.